Association of the ABO blood group with SARS-CoV-2 infection in a community with low infection rate (2021)
Background and objectives Reports on the association of the ABO phenotypes with infection by the SARS-CoV-2 virus have mostly come from countries with high infection rates. This study examined the possible association between SARS-CoV-2 infection and the ABO phenotype in Black Africa. Materials and methods This report is from a single centre where both asymptomatic and symptomatic patients were quarantined. At the time of this report, Oyo State, Nigeria had carried out 15 733 tests of which 3119 were positive for the virus with 1952 recoveries and 37 deaths. The ABO distribution of patients was compared with that of a blood donor population. Results Of the 302 participants, 297 (98%) had their blood group determined, asymptomatic and symptomatic individuals were 123 (40_7%) and 179 (59_3%) respectively. Blood group O was significantly less represented among the patients (P < 0_01) while blood groups B and AB were significantly more represented (P < 0_01, P = 0_03 respectively). Patients with anti-B (groups A and O) were significantly less represented than those without anti-B (B and/or AB): B and AB (P < 0_001), B (P = 0_002), AB (P = 0_01). There was no difference in the blood group distribution of symptomatic and asymptomatic patients (v2 (3, N = 302) = 2_29; P = 0_51), but symptomatic patients with anti-A (groups B and O) were more represented than asymptomatic patients with anti-A (v2 4_89; P = 0_03). Conclusion The higher prevalence of blood group O and more potent beta haemolysins (anti-B antibodies) are likely reasons for the lower infectivity by the SARS-CoV-2 virus and severity of COVID-19 disease in the community.